Nanomaterials in Advanced Batteries and Supercapacitors - Ozoemena, Kenneth I.; Chen, Shaowei (Nanostructure Science and Technology, 2016)
This book provides an authoritative source of information on the use of nanomaterials to enhance the performance of existing electrochemical energy storage systems and the manners in which new such systems are being made possible. The book covers the state of the art of the design, preparation, and engineering of nanoscale functional materials as effective catalysts and as electrodes for electrochemical energy storage and mechanistic investigation of electrode reactions. It also provides perspectives and challenges for future research. A related book by the same editors is: Nanomaterials for Fuel Cell Catalysis.